Which workers are more vulnerable to work intensification? An analysis of two national surveys. Issue 6 (7th September 2015) - John Burgess and Professor Julia Connell, Professor; Le Fevre, Mark; Boxall, Peter; Macky, Keith
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to identify whether there are particular employee groups that are more vulnerable to work intensification and its outcomes for well-being. Design/methodology/approach – This paper utilises data collected in two representative national surveys in 2005 (n=1, 004) and 2009 (n=1, 016), first to determine which employee groups are most vulnerable to work intensification and, second, to identify who is more vulnerable to the impacts of high work intensity on well-being, in terms of job (dis)satisfaction, stress, fatigue, and work-life imbalance. Findings – Professionals reported significantly higher levels of work intensity than all other occupational groups, and higher levels of stress and work-life imbalance. In addition, full-time employees experienced greater work intensity than part-timers, and union members than non-union members. Public-sector employees reported greater stress and work-life imbalance than those in the private sector. There was also a small, but significant and consistent, interaction effect that identified women as more negatively impacted by high work intensity than men. Research limitations/implications – Professionals have become vulnerable workers, in the sense of high levels of work demand, and the notion of worker vulnerability needs to recognise this. Future research on vulnerable employees would benefit from a broader conception of what constitutes vulnerability, exploring a wider range of employee groups who might be considered vulnerable, and including a wider range of potential outcomes for the lives and well-being of the individuals concerned. In particular, a more finely grained examination of the working conditions of professionals would be desirable, as would a more detailed examination of the reasons for the higher negative impact of work intensity on women. Practical implications – One way of improving the sustainability of professional working is to foster higher rates of part-time working, which brings better outcomes in terms of stress and work-life balance. This, however, is hardly a societal remedy and the question of how to reverse deteriorating job quality among professionals, particularly those struggling to balance work and family demands, is something that needs much greater attention. Originality/value – The paper expands the notion of "vulnerable workers" to recognise those groups most at risk of work intensification, and the outcomes of that intensification for satisfaction, stress, fatigue, and work-life balance. The authors add to the small group of studies highlighting the degradation of professional work, as well as identifying other types of employee who are more vulnerable to work intensification. The use of two large-scale surveys, with a four-year gap, has allowed a high degree of consistency in the patterns of vulnerability to be revealed.